The influence of renal insufficiency on in-hospital major adverse cardiovascular events in STEMI patients receiving primary percutaneous coronary intervention - Anjarwani, Setyasih; Nurudinulloh, Akhmad Isna; Widito, Sasmojo; Gunawan, Atma; Prasetya, Indra (Universitas Brawijaya, 2025)
Introduction: Renal insufficiency (RI) is related to poor clinical results in STEMI patients receiving primary percutaneous coronary interventions (PCI). Objectives: This study evaluates the effect of RI on in-hospital major adverse cardiovascular events (MACE) in STEMI patients receiving primary PCI. Methods: The study was predicated on the registry of 1447 STEMI patients from January 2020–December 2023. Study samples were categorized into two groups: RI (eGFR<60mL/min/1.73m²) and no RI (eGFR≥60mL/min/1.73m²). Patients’ characteristics and in-hospital MACE in the two groups underwent analysis. Results: Among 848 consecutive subjects, 238 (28%) had RI, and 610 (72%) had no RI. Age (p = 0.000), diabetes mellitus (p = 0.007), and onset STEMI>12 hours (0.043) were correlated with RI. Dyslipidemia (p = 0.025), Onset STEMI>12 hours (p = 0.006), and RI (p = 0.000) were correlated with MACE. RI was correlated with MACE (OR 2.04, 95% CI: 1.46–2.85, p = 0.000). RI was correlated with sub-group analysis of MACE; cardiogenic shock (OR 2.00, 95% CI: 1.34-2.99, p = 0.001), acute heart failure (OR 1.80, 95% CI: 1.22-2.65, p = 0.003), malignant arrhythmia (OR 2.40, 95% CI: 1.61-3.58, p = 0.000), and mortality (OR 2.74, 95% CI: 1.78-4.24, p = 0.000). Conclusions: RI was correlated with in-hospital MACE in STEMI patients receiving primary PCI. In a sub-group analysis of in-hospital MACE, RI constituted a strong independent predictor of cardiogenic shock, acute heart failure, malignant arrhythmia, and mortality, respectively.